Vertical gardens: Manufacturing materials proposal (Research, Society and Development, 2021)
Vertical gardens emerged with the aim of increasing green areas in large urban centres, thus reducing the negative impacts of this dense urbanization. In general, vertical gardens are able to improve air quality, reduce heat islands, increase biodiversity, among other advantages presented in this work. This study proposes the use of two materials for making panels for vertical gardens. The panels were based on the model developed by the French botanist Patrick Blanc, using “green felt” and “grey cacharel” with each panel measuring 50 x 80 cm and with 24 pockets. These were installed in a residence in the municipality of Ilha Solteira, São Paulo state, Brazil; having with vegetal species Trandescantia zebrina. During January 19 to February 2, 2020, the temperatures of the panels, the wall and the region behind the panels were measured. An average thermal damping of up to 8.71°C was observed; it was concluded that the panels developed were effective for the construction of vertical gardens.